Determination of polycyclic aromatic hydrocarbon metabolites in milk by a quick, easy, cheap, effective, rugged and safe extraction and capillary electrophoresis. Issue 14 (18th June 2013) - Knobel, Gaston; Campiglia, Andres D.
<x xml:space="preserve">Abstract</x> We describe the first application of a quick, easy, cheap, effective, rugged and safe extraction technique to the CZE analysis of monohydroxylated metabolites of polycyclic aromatic hydrocarbons in milk. Complete resolution of 2‐hydroxyfluorenene, 1‐hydroxynaphthalene, 2‐hydroxynaphthalene, 3‐hydroxyphenanthrene, and 9‐hydroxyphenanthrene was accomplished in 4 min of electrophoretic run. Limits of detection at the parts‐per‐billion were obtained with a single solvent (acetonitrile) for metabolite extraction and sample stacking. The small sample volume (1.2 mL) and the conservative usage of chemicals provided a simple and rapid procedure for the simultaneous extraction of numerous samples. Adding 4 min of electrophoretic run per sample, it should be possible to screen ten samples in approximately 1 h of analysis time. The nanoliter extract volume required for sample injection allows for further chromatographic usage and confirmation of positive samples. The unique electrophoretic pattern of the studied metabolites demonstrates the potential for the unambiguous determination of positional isomers with very similar chromatographic behaviors and undistinguishable mass fragmentation patterns.